EDUKASI PANGAN FUNGSIONAL DAN PELATIHAN PENGOLAHAN TEMPE MENJADI MAKANAN SEHAT PADA REMAJA - Oktavina Permatasari; Andrea Putri Sekar Tunjung; Zuhria Ismawanti (LPPM Universitas Bina Bangsa, 2023)
Adolescents have special nutrition needs compared to other age groups because they experience growth and physiological changes associated with puberty. The food consumed by adolescents must contain nutrients to meet daily needs. One of the problems of adolescents is the choice of food that is not based on nutritional content and food safety, but rather on social factors so as not to lose status. Consumption of junk food for a long time can cause nutritional problems that cause varying nutritional status. Based on these problems, it is necessary to have functional food education and training in processing tempeh into healthy food for adolescents aims to increase knowledge about healthy food based on functional food to be able to change food consumption patterns in adolescents. The method to provide functional food education and training in processing tempeh into healthy food with animated videos. Based on the results of the student evaluation, it obtained an increase in knowledge and students to notice intake of food consumed